MENAKAR PEMILIHAN UMUM KEPALA DAERAH SECARA DEMOKRATIS - Ade Kosasih (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Abstract: One of the implications of the amendment of the 1945 Constitution is the issue of General Election of Regional Head (Pemilukada). The regulation of Pemilukada towards a more democratic direction is motivated by previous election practices that have shortcomings and weaknesses in terms of democracy. According to Article 18 Paragraph (4) of the 1945 Constitution, the Regional Head “shall be elected democratically”, if interpreted may mean Pemilukada directly or through the election by the DPRD. The sentence is “elected democratically” to consider the implementation of Pemilukada in special and special areas. Thus, Pemilukada directly or through representative institutions is still said to be democratic, as long as the implementation of electoral principles consistently. These electoral principles are the benchmarks for measuring democratic elections. These principles include direct, public, free, confidential, and fair and just principles.Keywords: general election, Head of Region, democratic